Low Voltage Interior Permanent Magnet Synchronous Motor (IPM PMSM) Design for Agricultural Robot Drive - Ahmad Awaluddin Baiti; I Wayan Adiyasa; Muslikhin Muslikhin (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
The growing demand for autonomous agricultural robots requires compact, energy-efficient 12 V drives. This work designs a 12 V Interior Permanent Magnet Synchronous Motor (IPM PMSM) for field robots with targets of torque >0.8 Nm, speed >1000 rpm, and outer diameter <100 mm. Two rotor options—baselines 0° and 12° skew—were optimized and evaluated via finite-element analysis of torque, back-EMF, efficiency, and thermal behaviour. Compared with 0°, the 12° skew cut torque-ripple RMS from 0.2885 to 0.1390 Nm (−51.8%) and reduced cogging torque by >50%, while peak torque decreased only slightly (1.85 → 1.81 Nm; −2.4%). Efficiency remained high ( 89%), power factor improved (0.95 → 0.964), and passive cooling kept temperatures ≤65 °C at 60 minutes. These results indicate that a 12° skew provides a practical design trade-off for low-voltage agricultural PMSMs, delivering smoother, more stable torque for precision tasks such as seeding and spraying without sacrificing overall efficiency.